ANALISIS PERBEDAAN PERSEPSI KONSUMEN TERHADAP MEREK APLIKASI PESAN INSTAN WHATSAPP DAN LINE BERDASARKAN CITRA MEREK, FITUR, DESAIN DAN KELOMPOK ACUAN - Limbong, Abdi Eliakim Donlezi; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
This study aimed to analyze to find out if there is a difference in the perception of costumer from instant messaging application WHATSAPP and LINE. From this analysis can be known whether  there  is  a  difference  by  age  have  different  perceptions  or  have  same  perception  of application instant messaging WHATSAPP and LINE, also aims to analyze most dominant variable against consumerperception and most distinguishes variable between WHATSAPP and  LINE.The population taken in this research are consumers who ever use instan messaging WHATSAPP and LINE. Samples used in this research some 400 respondents used by non- probability   sampling   technique   with   approach   quota   sampling   (   the   sample   based   on predetermined amount). A method of analysisis used is quantitative ananlysis that is using Mann- Whitney U.The variable brand image is a factor that most distinguishes between instant mesagging aplication WHATSAPP and LINE with Z-value -2,857 then followed by feature of -2,221, design  of -2,118  and  group  referrence  of  -1,084.  Hypothesis  testing  is  done  using  Z  test  showed  that consumers perception of the difference from instant messaging application WHATSAPP and LINE occurred against the variable viewed from   brand image , feature and design. But consumer perception of differences did not happen to the variable viewed from group reference variable. While the most dominant perception based on WHATSAPP respondent are reference group while LINE respondents are brand  image  Costumer  age above 25  years old  have  more  preferable perception on WHATSAPP compared to who is aged 17-25 years old. Costumer aged 17-25 years old have more prefereable perception on LINE compared to who is aged above 25 years old.